Multimodal Rag Analysis Of Product Datasheet - David Lau Keat Jin; Ganthan Narayana Samy; Fiza Abdul Rahim; Nurazean Maarop; Mahiswaran Selvananthan; Mazlan Ali; Sundresan A/L Perumal (Razak Faculty of Technology and Informatics,UTM, 2024)
Non-Indexed Publication